2013
DOI: 10.1002/2013jb010340
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties and brittle strength of thermally cracked granite under confinement

Abstract: [1] Effects of thermal crack damage on the rupture processes of a fine-grained granite were investigated under triaxial stress, under water (wet) and argon gas (dry) saturated conditions, and at room temperature. Thermal cracking was introduced by slowly heating and cooling two samples of La Peyratte granite up to 700 ı C, which were compared to two intact specimens. For each rock sample, a hydrostatic test was first carried up to 90 MPa effective pressure (5 MPa constant pore pressure). The samples were then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
84
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 52 publications
(94 reference statements)
13
84
0
Order By: Relevance
“…As shown in Figure c, we recorded about 7 times less AE during the hydrostatic experiment performed in wet conditions than in dry conditions. Similar observations were made in low‐porosity crystalline rock (see, e.g., Wang et al, ). Two mechanisms at least could explain such differences: the increased attenuation in the presence of fluids (since the triggering threshold remained the same in all our experiments) and subcritical crack growth that would radiate less acoustic waves (triaxial creep experiments on sandstone have shown that an increased efficiency of stress corrosion cracking reduces the mechanical work required; i.e., there is an “energy deficit,” to bring a sample to failure; Brantut et al, ).…”
Section: Mechanical Datasupporting
confidence: 85%
See 1 more Smart Citation
“…As shown in Figure c, we recorded about 7 times less AE during the hydrostatic experiment performed in wet conditions than in dry conditions. Similar observations were made in low‐porosity crystalline rock (see, e.g., Wang et al, ). Two mechanisms at least could explain such differences: the increased attenuation in the presence of fluids (since the triggering threshold remained the same in all our experiments) and subcritical crack growth that would radiate less acoustic waves (triaxial creep experiments on sandstone have shown that an increased efficiency of stress corrosion cracking reduces the mechanical work required; i.e., there is an “energy deficit,” to bring a sample to failure; Brantut et al, ).…”
Section: Mechanical Datasupporting
confidence: 85%
“…Acoustic waveforms were amplified at 40 dB and recorded at 10 MHz sampling rate using a Richter system (Itasca Ltd.). A complete description of the acoustic system is given in Ougier‐Simonin et al () and Wang et al (). A classical ultrasonic pulse transmission technique was used for P wave velocity measurements.…”
Section: The Studied Limestone and Experimental Methodsmentioning
confidence: 99%
“…The variable effect of thermal stressing at similar temperatures has also been noted by changes in crack content in other rocks such as andesite (Heap et al, 2014a) and granite (Wang et al, 2013). Although heating and cooling can both induce cracking, there seems to be no systematic response as a function of starting porosity.…”
Section: Discussionmentioning
confidence: 82%
“…It is unlikely that the absence of foreshocks in all fluid‐pressurized conditions results solely from an increased attenuation of seismic waves since the sensors were located <1 mm away from the fault. Previous experiments have indeed shown that AEs are systematically observed prior to the failure of intact or thermally cracked, dry or water saturated granite specimens (Wang et al, ). The absence of recorded foreshocks in all fluid‐pressurized experiments might nevertheless be due to the high recording threshold of our AE triggered setup (0.001 V).…”
Section: Discussionmentioning
confidence: 90%